Mary Slessor--everybody's mother : the era and impact of a Victorian missionary - Hardage, Jeanette (Cambridge, U.K. : Lutterworth Press, 2010)
How did a petite redhead from the slums of Dundee become a role model for a hundred years? How did she come to wield influence in the land known to her compatriots as the white man's grave? Why are there statues of her holding twins in Nigeria' How did she develop her missionary fervor combined with down-to-earth common sense? How did she overcome difficult situations throughout her life in ways that set her apart from many Victorians? Her eccentricities are often cited: She climbed trees, marched barefoot and bareheaded through the forest, declined to filter her water, and shed her Victorian.
Preparing and going, 1848-1879. Early influences ; Duke Town -- Branching out, 1879-1890. Old Town : too busy ; A long pause : Creek Town ; Marsh fever and other afflictions ; Opening a territory -- New possibilities, 1890-1900. Escapades and romance ; Hopes and disappointments ; British imperial agents ; Visitors and empire -- Queen Mary, 1900-1909. Bairns ; Long juju ; A new man and new work ; Court and furlough ; Disagreements in and out of court -- A life spent, 1909-1915. Faith matters ; Ikpe and Nkana ; Rest and honor -- A legacy, 1915 and later. Endings ; Remembrance ; Epilogue: African mission to Liverpool.
Includes bibliographical references (pages 319-330) and index.
Print version record.
Master record variable field(s) change: 600
Keywords: Slessor, Mary, -- 1848-1915.; Church of Scotland -- Missions -- Nigeria -- Calabar Region; Slessor, Mary Mitchell, -- 1848-1915.; Church of Scotland -- Missions -- Nigeria -- Calabar; Women missionaries -- Nigeria -- Calabar Region -- Biography; Women missionaries -- Scotland -- Biography; Presbyterian Church -- Missions -- Nigeria -- Calabar Region; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Christian Ministry -- Missions; Electronic books